2004
DOI: 10.2519/jospt.2004.34.10.628
|View full text |Cite
|
Sign up to set email alerts
|

Upper Extremity Work-Related Musculoskeletal Disorders: A Treatment Perspective

Abstract: Numerous terms, including repetitive-stress injuries and cumulative-trauma disorders, have been used to describe what is now commonly termed work-related musculoskeletal disorders. The etiology of work-related musculoskeletal disorders is multifactorial and includes physical, individual, and psychosocial factors that contribute to the presenting symptoms. Prolonged positioning away from the ideal posture will affect neural and other soft tissues in the upper extremity. Abnormal postures and positions may resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 59 publications
0
11
0
1
Order By: Relevance
“…This may be attributed to occupational exposure to repetitive work tasks, prolonged sedentary postures, heavy lifting, intensive-physical labour and long working hours. Several studies have also identified behavioural factors such as obesity, physical inactivity, poor diet and substance abuse as being closely associated with the development of LBP and occupation related RSI [6,7]. …”
Section: Introductionmentioning
confidence: 99%
“…This may be attributed to occupational exposure to repetitive work tasks, prolonged sedentary postures, heavy lifting, intensive-physical labour and long working hours. Several studies have also identified behavioural factors such as obesity, physical inactivity, poor diet and substance abuse as being closely associated with the development of LBP and occupation related RSI [6,7]. …”
Section: Introductionmentioning
confidence: 99%
“…Muscle imbalance, defined as predominance of one of a synergist pair of muscles during a movement [3], has become an important topic in the etiology of many musculoskeletal disorders [4]. The shoulder muscles do not gain equally in strength during wheelchair propulsion; only those active in the push phase become stronger, whereas those active in the recovery phase remain at the same level of strength.…”
Section: Introductionmentioning
confidence: 99%
“…However, eliminating overhead work tasks is not Assuming a stationary and constrained working posture is considered an important risk factor for work-related musculoskeletal disorders [8]. Muscle imbalance, defined as the predominance of one of the synergist pairs of muscles during a movement [14], has become an important topic in the etiology of many musculoskeletal disorders [15]. This study analyzed the problem of shoulder fatigue from a static perspective.…”
Section: Introductionmentioning
confidence: 99%